Extraction of Radix trichosanthis Polysaccharides for Potential Antihyperlipidemic Application. (11th April 2022) - Chen, Fujia; Xu, Yilin; Ding, Nana; Li, Hongyan; Li, Tongbiao; Liu, Fengyun; Liang, Mengxue; Song, Li; Liu, Junhe; Li, Enzhong; Liu, Jiayang
Abstract : This study focused on the optimization of ultrasound-assisted compound enzyme extraction for polysaccharides (RTPs) from Radix trichosanthis by orthogonal experiment and response surface methodology, and then its extraction kinetics model and antihyperlipidemic activities were studied. The optimum extraction process was as follows: cellulase—1.0%, papain—1.0%, pectase—0.5%, pH—5, extraction temperature—50°C, and liquid-to-solid ratio—30 mL/g; prediction value of RTPs was 7.54%; the experimental yield of RTPs was 7.22%, while 50 minutes was optimized in Weibull kinetics model. Then high-dose groups of RTP extract could reduce the TC, TG, and LDL-C levels and increase the level of HDL-C in high-fat mice, with the ability to lower the MDA content and enhance SOD level.